2011
DOI: 10.1097/mjt.0b013e3181b809ee
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Revascularization Strategy for ST Elevation Myocardial Infarction with Multivessel Disease: Experience and Results at 1-Year Follow-Up

Abstract: Primary percutaneous coronary intervention (PCI) of culprit lesions (CLs) is the standard of care in patients presenting with ST elevation myocardial infarction (STEMI). However, optimal revascularization strategy for significant nonculprit lesions (non-CLs) in the setting of STEMI remains controversial. The importance of defining of such a strategy lies in the fact that approximately 50% of patients with STEMI have multivessel disease (MVD). The aim of this study was to describe characteristics, therapeutic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Overall, seven studies reported long-term MACE [10,25,27–30,32,34]. There was a trend toward reduced risk of MACE with S-PCI compared with MV-PCI with no heterogeneity, although the trend did not reach statistical significance (OR 0.83, 95% CI 0.62–1.12, P = 0.22, I 2 = 0%), as shown in Fig 4.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Overall, seven studies reported long-term MACE [10,25,27–30,32,34]. There was a trend toward reduced risk of MACE with S-PCI compared with MV-PCI with no heterogeneity, although the trend did not reach statistical significance (OR 0.83, 95% CI 0.62–1.12, P = 0.22, I 2 = 0%), as shown in Fig 4.…”
Section: Resultsmentioning
confidence: 96%
“…Six studies reported long-term repeat myocardial infarction (re-MI) after long-term follow-up [10,25,27,29,32,34]. There was no significant difference between S-PCI and MV-PCI.…”
Section: Resultsmentioning
confidence: 99%
“…The staged PCI strategy was defined as PCI confined to culprit vessel lesions only, after which Ն1 lesions in nonculprit vessel were treated during planned secondary procedures. The timing of staged PCI procedures was defined as reported in each study (Table 1) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…In this analysis, staged PCI has also been found to be superior to multivessel PCI during the index event. The studies carried out by Politi et al [10], Corpus et al [7], Hannan et al [4], Varani et al [20] and Mohamad et al [21] were included in this analysis, yielding better results with the staged PCI strategy. Only Varani et al [20] found a statistically significant benefit from the staged PCI strategy; the other authors have found better results with staged PCI than multivessel PCI, but these findings were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%